THE EFFECTIVENESS OF THE IMPLEMENTATION OF THE FAMILY PLANNING VILLAGE (KB) PROGRAM IN NORTH BENGKULU REGENCY - Dimas Prima Yuda; Edi Darmawi; Alexander (Yayasan Wayan Marwan Pulungan, 2024)
In improving the quality of life of the community at the village level or equivalent, KB Villages were formed. Through the Kampung KB program, it is hoped that it can improve the welfare of the community. With the existence of the Kampung KB program, which was originally less public awareness in terms of social awareness, it is now starting to grow again. This study aims to determine the effectiveness of the implementation of the Family Planning Program in North Bengkulu District. This study uses a quantitative method and uses a questionnaire data collection technique that is distributed to respondents from residents of Aur Gading Village who are actively participating in the family planning program, through random sample sampling. The researcher's data analysis technique uses a simple regression test through SPSS 27. The results of the study showed that the significant value of the effectiveness of the program implementation was 0.00 < 0.05 so it can be concluded that the variable of the Effectiveness of the Implementation of the KB Village Program (X) has an effect in North Bengkulu Regency (Y). concluded that there was a positive and significant influence on the effectiveness of the implementation of the KB Village program in North Bengkulu Regency. This means that the more effective the implementation of the KB Village program, the more the welfare of the community will also increase, and vice versa.